Whose ageism? The reinvigoration and definitions of an elusive concept. Issue 3 (2nd July 2016) - Snellman, Fredrik
Abstract: This article deals with a critical conceptual understanding of ageism. It does so foremost by problematizing some of the inadequacies in a previously published article that introduces a new definition of the concept ageism. Attention is devoted to (i) the prima facie that the ageism concept is repeatedly underscored as a concept for older people exclusively and the "us-them" distinction; (ii) what the concept ageism means and different ways of defining ageism; and, (iii) different ways in which we desire to study ageism. The article finishes with a simple example in which ageism is compared to a box of chocolates. The example is used to illuminate how we can carry out anti-ageist work more effectively in society. That is, to help us understand and sometimes avoid the different and relative inferiorities that follow with different ages, in order to come to grips with the different and relative inferiorities that is often assumed to come with old age.